Public safety network design for broadband wireless access - Sümer, Ahmet Sacid; Yılmaz, Talha; Memisoglu, Ebubekir; Akkurt, Arif; Arslan, Hüseyin (Frontiers in Communications and Networks, 2023)
Public protection and disaster relief (PPDR) agencies rely on wireless communications to respond in the event of emergencies. Public safety networks (PSNs) provide the wireless network used by emergency services. PSN is used to support push-to-talk services with some data transmission by employing land mobile radios. However, PPDR agencies are increasingly relying on additional information such as videos that require higher bandwidths. Therefore, many countries are transitioning or integrating their public safety networks with advanced broadband wireless communication systems such as fourth-generation (4G) long term evolution (LTE) and planning to evolve to fifth-generation (5G) new radio (NR) in the future. The paper investigates infrastructure sharing mechanisms, coexistence, and deployment strategies in the PSNs' transition to a 4G LTE network. We also examine the LTE-based PSN deployment scenarios in different countries. Furthermore, the advantages and disadvantages of various sharing mechanisms and coexistence schemes are discussed.